Why STM Can Be More Than A Research Toy. - DRAGOJEVIĆ, ALEKSANDAR; FELBER, PASCAL; GRAMOLI, VINCENT; GUERRAOUI, RACHID (Communications of the ACM, 2011)
The article discusses computer software transactional memory (STM) and its performance capabilities compared to sequential code. Aspects of multicore architectures, concurrent programming, the transactional-memory (TM) paradigm, and computer hardware transactional memory (HTM) are discussed. The article notes that TM systems are not expected to become commercially available for a few years. The article discusses the ability of STM to offer TM functionality while avoiding the limitations of HTM. A summary of key insights offered in the article is presented.